Sero-epidemiological survey of Coxiella burnetii in livestock and humans in Tana River and Garissa counties in Kenya. - Damaris Mwololo; Daniel Nthiwa; Philip Kitala; Tequiero Abuom; Martin Wainaina; Salome Kairu-Wanyoike; Johanna F Lindahl; Enoch Ontiri; Salome Bukachi; Ian Njeru; Joan Karanja; Rosemary Sang; et al. (PLoS Neglected Tropical Diseases)
Background Coxiella burnetii is a widely distributed pathogen, but data on its epidemiology in livestock, and human populations remain scanty, especially in developing countries such as Kenya. We used the One Health approach to estimate the seroprevalance of C. burnetii in cattle, sheep, goats and human populations in Tana River county, and in humans in Garissa county, Kenya. We also identified potential determinants of exposure among these hosts. Methods Data were collected through a cross-sectional study. Serum samples were taken from 2,727 animals (466 cattle, 1,333 goats, and 928 sheep) and 974 humans and screened for Phase I/II IgG antibodies against C. burnetii using enzyme-linked immunosorbent assay (ELISA). Data on potential factors associated with animal and human exposure were collected using a structured questionnaire. Multivariable analyses were performed with households as a random effect to adjust for the within-household correlation of C. burnetii exposure among animals and humans, respectively. Results The overall apparent seroprevalence estimates of C. burnetii in livestock and humans were 12.80% (95% confidence interval [CI]: 11.57-14.11) and 24.44% (95% CI: 21.77-27.26), respectively. In livestock, the seroprevalence differed significantly by species (p < 0.01). The highest seroprevalence estimates were observed in goats (15.22%, 95% CI: 13.34-17.27) and sheep (14.22%, 95% CI: 12.04-16.64) while cattle (3.00%, 95% CI: 1.65-4.99) had the lowest seroprevalence. Herd-level seropositivity of C. burnetii in livestock was not positively associated with human exposure. Multivariable results showed that female animals had higher odds of seropositivity for C. burnetii than males, while for animal age groups, adult animals had higher odds of seropositivity than calves, kids or lambs. For livestock species, both sheep and goats had significantly higher odds of seropositivity than cattle. In human populations, men had a significantly higher odds of testing positive for C. burnetii than women. Conclusions This study provides evidence of livestock and human exposure to C. burnetii which could have serious economic implications on livestock production and impact on human health. These results also highlight the need to establish active surveillance in the study area to reduce the disease burden associated with this pathogen.